Moiré microstructure generated binary amplitude gratings for suppression of high diffraction orders. (December 2021) - Patorski, Krzysztof; Cywińska, Maria; Zdańkowski, Piotr; Trusiak, Maciej
Highlights: Application of the theory of moiré fringes formed by multiplicative superimposition of two binary amplitude gratings with selected opening numbers (the theory was originally proposed by K. Patorski several years ago) to generate novel diffraction grating with the subtractive and additive moiré microstructures providing quasi-sinusoidal transmittance in orthogonal directions. Detailed comparative studies of the Fourier spectra of the proposed grating with the structures reported in the literature, i.e., the inclined rectangular aperture grating (IRAG) and the grating with hexagonal holes. Application of the multiplicative and additive moiré superimposition techniques using various binary structures for generation of the IRAG and hexagonal holes gratings with suppressed high diffraction orders (square, checker, triangle and hexagonal lattices). Original numerical simulations/visualizations and experimental validation corroborating theoretical findings. Abstract: We propose 2D gratings with 2D sinusoidal-like transmittance for spectral analysis in a wide wavelength range. Our design deploys the concept of the multiplicative superimposition of two mutually inclined or orthogonally crossed 1D binary amplitude gratings with appropriately selected opening numbers. In result the trapezoidal transmittance function without the 3 rd and even harmonics is obtained in two perpendicular directions corresponding to the so-called subtractive and additive moiré patterns. The distance between main diffraction orders, i.e., -1, 0 and +1 in both directions is easily controlled by adjusting the angle between component grating lines. The moiré microstructure acting as 2D diffraction grating comprises 4 sided parallelogram holes up to the angle of 90 degrees for which they become rectangles. Diffraction efficiencies and free-standing parameters of our grating and the solutions reported in the literature, i.e., the inclined rectangular aperture grating (IRAG) and the grating with hexagonal holes are calculated and compared. Additionally, the methods of design for the literature reported gratings which start from square or rectangular shape apertures are introduced for the sake of comprehensive treatment of gratings with suppressed high diffraction orders. Design considerations are corroborated by the moiré Fourier spectra numerical simulations, their visualizations and experimental works.